Analysis of Socio-Demographic Factors Influencing Family Latrine Utilization Behaviour - Erna Hartatik; Rondhianto Rondhianto; Dina Helianti (NurseLine Journal, 2023)
Background: Providing healthy latrines for each family is an effort to reduce open defecation. However, there are still many open defecation incidents, which can increase the risk of fecal-oral transmission of disease. Many factors influence open defecation behavior, one of which is socio-demographic factors. Purpose: This study aims to analyze socio-demographic factors' influence on family latrine utilization behavior. Method: This type of research is observational analytic with a cross-sectional design. The sample size was 138 respondents using the cluster random sampling technique. The independent variables are age, gender, education, income, and number of family members. Meanwhile, the dependent variable is the behavior of using the family toilet. The instrument used was a questionnaire that was analyzed using multiple logistic regression and mean difference tests. Results: Most respondents were aged 41 – 60 years (73.2%), women (57.3%), secondary education (55.8%), with family members of less than four people (81.88%), and all respondents earned less than the minimum wage (100%). Most respondents had family latrine utilization behavior in the high category (66.7%). The modeling test showed the model fit (p = 0.034; R2 = 0.162). It showed that age, gender, education, income and number of family members simultaneously significantly affect family latrine utilization behavior by 16.2%. However, partially, only the educational factor had a significant effect (p=0.001). In addition, the mean difference test shows significant differences in family latrine utilization behavior based on age and education level (p=0.002; p=0.001). Conclusions: The socio-demographic factor that significantly influences latrine use behavior is the level of education. In carrying out health promotion efforts to increase family latrine utilization behavior, health workers should consider educational level factors to achieve the goal and reduce open defecation behavior.